A study of farmers’ motivation to participate in Pasar Tani / Azeana Abdul Rashid - Abdul Rashid, Azeana (Faculty of Business and Management, 2009)
This project paper focused on the research of ‘A Study of Farmers Motivation to Participate in Pasar Tani. The aim of this study is to examine the relationship between demographic variable and the reason for farmers’ market as sale outlet. The focusing of study has been stated on in price, quality, infrastructure, successful attribute farmers’ market, and advantages of farmers’ market. Meanwhile, this research also wants to determine the most important factors that influence farmers’ to participate in Pasar Tani. Not only that, the researcher also wants to identify the relationship between infrastructure and the advantages of Pasar Tani. The researcher also wants to identify the relationship between quality and price. The research is conducted using probability sampling method is simple random sampling. 77 sets of questionnaire have been distributed to the respondents in order to fill out the entire questionnaire. The result will be gain after the analysis and interpretation of data used through the Statistical Packages for Social Science (SPSS) Program version 14.0. The respondents mostly are the farmers who have participate in Pasar Tani in Melaka area. From the analysis, the researcher found that the reason for farmers choose Pasar Tani to market their product because of the benefit of Pasar Tani such as convenience place, strategic location, easy parking and many more. Some recommendation has been recommended to FAMA in order to be Pasar Tani are effective for the future.